1975
DOI: 10.1530/jrf.0.0430249
|View full text |Cite
|
Sign up to set email alerts
|

Components of Human Split Ejaculates

Abstract: Summary. The concentrations of spermatozoa, fructose, IgG, IgA, albumin, lactoferrin, transferrin, secretory piece of IgA, \ g=b\ 1C/ \ g=b\ 1A\ x=r eq-\ globulin (C\m='\3-component of complement), ceruloplasmin and fibrinogen were evaluated in human split ejaculates and/or in whole human seminal plasma. The concentrations of spermatozoa, IgG, IgA, albumin and transferrin decreased from the first portion of the split ejaculate to the last, indicating that these proteins originate mostly from secretions other t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Table 1 shows that the IGF-I/SM-C content in samples from vasectomized or azoospermic pa¬ tients (2 subjects in each category) was approxi¬ mately 60% lower than that in subjects with normal sperm densities. In split ejaculates from 2 normal subjects, the early (predominantly testicular) frac¬ tion (Tauber et al 1975) contained approximately 60% of the total activity. These observations sug¬ gest that 60% of the IGF-I/SM-C in SP is of testicular origin.…”
Section: Figurementioning
confidence: 99%
“…Table 1 shows that the IGF-I/SM-C content in samples from vasectomized or azoospermic pa¬ tients (2 subjects in each category) was approxi¬ mately 60% lower than that in subjects with normal sperm densities. In split ejaculates from 2 normal subjects, the early (predominantly testicular) frac¬ tion (Tauber et al 1975) contained approximately 60% of the total activity. These observations sug¬ gest that 60% of the IGF-I/SM-C in SP is of testicular origin.…”
Section: Figurementioning
confidence: 99%
“…The seminal vesicle has an important role in sperm function. 6,7 If inflammation of the seminal vesicles can be caused by C. trachomatis, this suggests that chlamydial seminal vesiculitis may be one of the causes of male infertility.…”
Section: Discussionmentioning
confidence: 99%
“…Naz et al [129] found that systemic intraperitoneal injection of MA-24 ascites fluid in mouse models reduced the percentage of fertilized ova (from 69% in untreated to 29% in treated), thereby reducing the fertility in vivo [130]. For determining the in vivo contraceptive efficacy of MARS, the antibodies were incubated in vitro with a defined volume of semen, followed by insemination of females.…”
Section: Immunocontraceptionmentioning
confidence: 99%